Determination of national midwifery ethical values and ethical codes: In Turkey - Ergin, Ayla (Nursing ethics, 2013)
It is important to define and practice ethical rules and codes for professionalisation. Several national and international associations have determined midwifery ethical codes. In Turkey, ethical rules and codes that would facilitate midwifery becoming professionalised have not yet been determined. This study was planned to contribute to the professionalisation of midwifery by determining national ethical values and codes. A total of 1067 Turkish midwives completed the survey. The most prevalent values of Turkish midwives were care for mother–child health, responsibility and professional adequacy. The preferred professional codes chosen by Turkish midwives were absence of conflicts of interest, respect for privacy, avoidance of deception, reporting of faulty practices, consideration of mothers and newborns as separate beings and prevention of harm. In conclusion, cultural values, beliefs and expectations of society cannot be underestimated, although the international professional values and codes of ethics contribute significantly to professionalisation of the midwifery profession.